The role of supervision of school principal as an effort to improve teacher professionalism in teaching - Herlinawati, Herlinawati; Kristiawan, Muhammad; Alforqi, Alforqi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The principal is a leader in educational institutions that regulates and manages educational activities in schools. Therefore, school principals play an important role in improving the quality of education, especially improving teacher performance to be more enthusiastic and professional in teaching and developing themselves who are in charge of delivering lessons to students. This study aims to identify the role of principal supervision as an effort to improve teacher professionalism in teaching at public high school (SMA Negeri) 10 OKU. This research was conducted at SMA Negeri 10 OKU. The research was carried out for 3 (three) months, starting from September 2020 to November 2020. The research method used was a qualitative descriptive method. Data collection techniques used include: (1) Interview or Interview; (2) Observation; (3) Documentation. Based on the research results, it was concluded that the principal had a role in the supervision carried out as an effort to improve teacher professionalism in teaching. It is known: (1) The role of principal supervision is evidenced by the teacher in planning lesson plans which are made reported and approved by the principal and according to the curriculum; (2) The role of principal supervision is proven by the teacher in carrying out the learning process in accordance with the learning device guidelines and using teaching aids; (3) The role of principal supervision is evidenced by the teacher evaluating the learning outcomes and reporting to the principal; (4) The role of principal supervision is evidenced by the teacher following up on the learning outcomes in accordance with the direction of the principal; (5) The role of principal supervision is evidenced by the teacher providing guidance to students.